(3TQM CHjGJ GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde Jcf fYde bGd Gdabjg GdHWdjhS cJGH GdLed CQOJ Cf CJHY Pdc GdcdGe s
(3BNQgG (B:s
(3BNQ GdehLhO ajg TQM bhd GdaQROb aeG SHb GdbjS ef ShA SjQI hdcf WaJ YdeGA YRdI NGdO s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(1701 (3c(B) s
Keywords: (3GdfMhs